ADHD Symptoms Increase Perception of Classroom Entropy and Impact Teacher Stress Levels - Rosa Angela Fabio; Carmela Mento; Antonio Gangemi; Giulia Picciotto (MDPI AG, 2023)
Attention deficit hyperactivity disorder (ADHD) is a common neuropsychiatric disorder among school-age children, characterized by persistent behavioral patterns of inattention and/or hyperactivity/impulsivity. These behaviors can create stress for teachers and negatively affect teacher-student interactions. This study hypothesized that a high frequency of ADHD students in the classroom can increase internal and external entropy, ultimately resulting in a negative stress impact on teachers. The physical concept of entropy, which measures the degree of disorder in a system, was used to better understand this relationship. The study evaluated 177 primary school teachers in their response to interacting with students with ADHD, using the Measurement of Psychological Stress (MPS) to evaluate subjective stress levels and the QUEIs and QUEIp questionnaires to measure structural and personal entropy. Path analysis was applied to identify the factors associated with the total score of MPS. The hypothesis was confirmed, as the frequency of ADHD students had a negative impact on teachers' entropy levels and personal entropy was found to significantly increase stress levels. The study highlights the negative impact of ADHD symptoms on stress levels and personal entropy of teachers when interacting with students with ADHD. These findings suggest the need for interventions aimed at balancing the frequency of students with ADHD and promoting positive training on stress reduction for teacher-student interactions.